2019
DOI: 10.21580/economica.2019.10.1.3186
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Crowdfunding Structure in Islamic Venture Capital for SMEs Development

Abstract: <p>SMEs that play significant role in Indonesia economy still suffer from financial constraint. Even though government provides big support to open finance access for SMEs, there are still more than half are not supported by sufficient access of financing. This paper investigates the possible financing methods that can be used by SMEs by examining its positive and negative aspects along with the shariah view on it. Since there are limitations that have to be removed, we propose new scheme of financing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The decrease in national growth means a small increase or even a decrease in the income of business revenue. It is important to note that more than 90% of business players in Indonesia are SMEs and thus are characterized by many types of constraints to accessing the financial pool (Athief, 2019). Thus, SMEs who suffered a lot during the pandemic will find their selves hard to generate revenue or get financial access in order to survive and pay their obligations.…”
Section: Imfis Resilience In the Pandemic Periodmentioning
confidence: 99%
“…The decrease in national growth means a small increase or even a decrease in the income of business revenue. It is important to note that more than 90% of business players in Indonesia are SMEs and thus are characterized by many types of constraints to accessing the financial pool (Athief, 2019). Thus, SMEs who suffered a lot during the pandemic will find their selves hard to generate revenue or get financial access in order to survive and pay their obligations.…”
Section: Imfis Resilience In the Pandemic Periodmentioning
confidence: 99%
“…The authors suggested also that IVC firms should include additional conditions in "Musharaka" and "Mudharaba" contracts such as a compensation to be paid in the case of the breach of the contract. In addition, Athief (2019) proposes to combine both IVC and crowdfunding. The idea lies in having additional IMEFM 15,6 income, which comes from the service provided by the IVC firm through publishing the selected company on its website in the form of equity crowdfunding campaign on the one hand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the results of the Dynamic LQ analysis, the information technology sector in Cirebon Regency grew negatively, this was because the growth of the same sector in other regions in West Java Province grew much faster. MSME performance will be more optimal when supported by all parties including financial institutions and banks (Athief, 2019). Based on ("PP No.…”
Section: Figure 1 Map Of the Leading Sector Of Cirebon Regency In 2018mentioning
confidence: 99%